Longevity of 2- and 3-surface restorations in posterior teeth of 25- to 30-year-olds attending Public Dental Service—A 13-year observation. (July 2017) - Palotie, Ulla; Eronen, Anna K.; Vehkalahti, Kimmo; Vehkalahti, Miira M.
Abstract: Objectives: The aim of this patient document-based retrospective study among 25- to 30-year-old Finnish adults was to evaluate longevity of 2- and 3-surface posterior restorations according to type of tooth, size of restoration, and restorative material used. Methods: Data were extracted from electronic patient files of the Helsinki City Public Dental Service (PDS), Finland. A total of 5542 2- and 3-surface posterior composite and amalgam restorations were followed indirectly from 2002 to 2015. Longevity of restorations was illustrated using Kaplan-Meier curves. Annual failure rates (AFRs) of the restorations were calculated separately by type of tooth, size, and material. Differences in longevity were statistically tested with log-rank tests. Results: Composite restorations formed the majority (93%). The longest median survival times and the smallest failure rates were found for teeth in the upper jaw, for premolars, and for 2-surface restorations. Median survival time of all restorations was 9.9 years (95% CI 9.6, 10.2) and re-intervention of restorations occurred less often in the maxilla (AFR 4.0%) than in the mandible (AFR 4.7%). Median survival time of composite restorations was greater for 2-surface than for 3-surface restorations: in premolars 12.3 vs. 9.6 years (p < 0.001) and in molars, 9.2 vs. 6.3 years (p < 0.001); for molar amalgams the difference (8.0 vs. 6.3 years) was non-significant (p = 0.38). Median survival time of 2- and 3-surface restorations in premolars exceeded that in molars (12.0 vs. 8.7 years; p < 0.001). Conclusions: Longevity of posterior composite multisurface restoration is comparable to amalgam longevity. Clinical significance: Regarding material choices for posterior multisurface restorations, composite and amalgam perform quite similarly in molars, 3-surface restoration being challenge for both materials.